PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP PENJUALAN PRODUK STARBUCKS JATIWARNA KOTA BEKASI - Retya Syafa Suwandi; Amanda Setiorini (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study was conducted to determine whether or not there is an effect of promotion and product quality on sales product either simultaneously or partially at Starbucks Jatiwarna, Bekasi. The study was conducted on respondents to customers of Starbucks Jatiwarna, Bekasi. Obtaining data using a questionnaire with a semantic differential scale. The sampling technique used is accidental sampling analysis. From the results of tests conducted found the fact that promotion and product quality simultaneously have a significant effect on sales product. In addition, promotion and product quality partially also have a significant effect on sales product.